Sense of Community and Emotional Regulation: Interconnections Leading to Flourishing Among Single Catholics - Tambun, Ivy Novenatha Karolina; Nanik, Nanik; Sampe Tondok, Marselius (Bulletin of Counseling and Psychotherapy, 2024)
Modernization and individualistic culture have shifted the values and expectations of the younger generation regarding marriage, leading to delays or decisions not to marry. However, in Indonesia, many single individuals still face social pressure due to societal stigma, as well as religious and cultural values. This pressure can negatively impact the well-being or flourishing of single individuals. This study aims to examine the relationship between sense of community and emotion regulation (cognitive and expressive suppressions) with flourishing among single individuals, using a correlational quantitative method with 105 respondents (Mage = 34.90; SD = 5.84 years) from the Catholic Singles Community “J”. A purposive sampling technique was employed to select the sample. The results of multiple correlation indicated that sense of community and emotion regulation together significantly positively correlate with flourishing (R = 0.293, R2 = 0.086, p < 0.05. Nevertheless, partial correlation analysis revealed a significant positive correlation between the sense of community and flourishing (p<0.05), but a non-significant correlation between emotion regulation (both cognitive and expressive suppression) and flourishing (p>0.05). Although emotion regulation did not directly correlate with flourishing, emotion regulation (cognitive and expressive suppression) were significantly positively correlated with most aspects of sense of community. The implications of this research suggest that enhancing the sense of community plays a crucial role in achieving flourishing among members of a community. Sense of community can be further strengthened when supported by emotion regulation skills within the community context.